(untitled) (Cardiovascular Journal, 2021)
Over the last one-year COVID 19 has affected millions of people around the world. Though initially it was thought to be an infection of respiratory system, but it involves any organ of the body. Its morbidity and mortality are more when it involves patients with preexisting cardiovascular diseases and also when it causes a cardiovascular complication. COVID 19 can produce a number of cardiovascular complications including myocardial infarction, heart failure, myocarditis, arrhythmia, thromboembolism etc. Following recovery from COVID 19 infection evaluation, follow up and management of these cardiovascular conditions, which may be sometimes in subclinical form, is essential. Though there is lack of adequate studies or guidelines, we tried to discuss the different aspects of Post- COVID cardiovascular care depending on the existing evidence and previous guidelines. Cardiovasc. j. 2021; 13(2): 189-199